English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

Very easy question!

You know the answer is
2X-3 or 2X+1 because you are given -1/2 and 3/2.
2X-3=0 2X+1=0
2X=3 2X=-1
X=3/2 X=-1/2

Then (2X-3)(2X+1)=0
4X^2+2X-6X-3=0
4X^2-4X-3=0
4X^2+kX-3=0

Therefore, k=-4.

If I am right remeber to put me as the best answer.
Thanks and good luck with your HW.

2007-09-02 18:26:23 · answer #1 · answered by Kenndy 3 · 0 0

4x² + kx – 3

To get the roots, the factors must be:
(2x + 1)(2x - 3)

k = 2 * 1 + 2 * -3
...= 2 - 6
...= -4

2007-09-02 18:19:59 · answer #2 · answered by gebobs 6 · 0 0

x = -1/2 and x = 3/2

2x = -1 and 2x = 3

2x +1 and 2x -3

(2x +1)(2x-3)

4x² - 6x + 2x - 3

4x² - 4x- 3


k = -4

2007-09-02 18:24:49 · answer #3 · answered by roOt 3 · 0 0

fedest.com, questions and answers